Fibroblast Reprogramming in Gastrointestinal Cancer - Melissari, Maria-Theodora; Chalkidi, Niki; Sarris, Michalis E.; Koliaraki, Vasiliki (Frontiers in Cell and Developmental Biology, 2020)
Gastrointestinal cancers are a significant cause of cancer mortality worldwide and have been strongly linked with chronic inflammation. Current therapies focus on epithelial/cancer cells; however, the importance of the tumour microenvironment in the development and treatment of the disease is also now well established. Cancer-associated fibroblasts (CAFs) are a major component of the tumour microenvironment and are actively participating in tumour initiation, promotion and metastasis. They structurally and functionally affect cancer cell proliferation, tumour immunity, angiogenesis, extracellular matrix remodelling and metastasis through a variety of signalling pathways. CAFs originate predominantly from resident mesenchymal cells, which are activated and reprogrammed in response to cues from cancer cells. In recent years, chronic inflammation of the gastrointestinal tract has also proven an important driver of mesenchymal cell activation and subsequent CAF development, which in turn are capable of regulating the transition from acute to chronic inflammation and cancer. In this review, we will provide a concise overview of the mechanisms that drive fibroblast reprogramming in cancer and the recent advances on the downstream signalling pathways that regulate the functional properties of the activated mesenchyme. This new mechanistic insight could pave the way for new therapeutic strategies and better prognosis for cancer patients.